Ruins and Desire: Interview with Pamela L. Jennings - WELBON, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In the 1990s I lived in New York City. I moved to New York City shortly after graduating from Oberlin College, in Ohio. I lived there for almost a de cade, and during that time I was very actively engaged in continuing my pursuit of a career in photography. Photography was my first form of visual art going back to junior high school. I enrolled in the New York University International Center for Photography master’s program because I really wanted to understand what it was to be a photographer. At that time I was very interested in street photography.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Birth of a Notion: Toward Black, Gay, and Lesbian Imagery in Film and Video - Parkerson, Michelle (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In mainstream media, gays and lesbians of color are either woefully present or predictably absent. The litany of black gay and lesbian characters in Hollywood films and network television reads like its own form of blackface. They range from the burly, black “bulldagger” as whore house madam in the 1933 film The Emperor Jones (starring Paul Robeson) to the predatory lesbian vamp in Spike Lee’s 1983 She’s Gotta Have It ; from Eddie Murphy’s ultracamp Miss Thing hairdresser on NBC’s Saturday Night Live to the snap! queen duo on Fox TV’s In Living Color. These relentless stereo types are part of
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Construction of Computation and Desire: Introduction to Yvonne Welbon’s Interview with Pamela L. Jennings - Keeling, Kara (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Early in the following interview, Pamela Jennings explains to Yvonne Welbon that her work gradually expanded from an initial and abiding interest in street photography toward working with and through forms of computational media. Jennings equates her move toward what she describes as “computational-based creative expression” with her growing interest in multimedia throughout the early 1990s, and she uses the term multimedia as a way of marking her work in a variety of different media and her interest specifically in computational media because the formulation computational media was not available to her then. The compelling relationship Jennings narrates between her
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Producing Black Lesbian Media - Moore, Candace (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In interviews the comedian Wanda Sykes describes being a successful black, openly gay woman in Hollywood as akin to being a unicorn. Clearly Sykes is majestic. Yet her joke hinges on a bitter truth: the mainstream media industry grants few women, not to mention lesbians of color, access to power. Despite shifts in the cultural imaginary around civil rights, Hollywood continues to maintain an embarrassing lack of diversity in its labor force, especially at decision-making levels. To battle this long-standing reputation, studios have developed diversity-hiring programs.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

From Rage to Resignation: Reading Tina Mabry’s Mississippi Damned as a Post–Civil Rights Response to Nina Simone’s “Mississippi Goddam” - Moore, Marlon Rachquel (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Much has been written about Nina Simone’s song “Mississippi Goddam” because it lyrically achieves the political consciousness of the embattled community whose experiences and energy it intends to speak to, through, and for. With its curse words, impatient tone, and energetic rhythm, it could never be mistaken for the traditional, Christian-inflected civil rights dirge. “Alabama’s got me so upset,” the chorus complains. “Tennessee made me lose my rest, and,” as if its atrocities need not be spelled out, “every body knows about Mississippi, goddam!” The song was banned from radio airplay but still became part of the civil rights sound
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Narrating Our History: An Introduction - Harris, Thomas Allen (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Around 1994 or 1995 I came across a call for articles for an anthology to be published by the XII Black International Cinema , documenting ten years of the festival and associated activities, 1986– 95. The request asked for articles and film lists from an international and intercultural group of scholars and filmmakers, and I thought this was an opportunity to document the exciting and pioneering work that was being done by a community of emerging Black lesbian and gay film-and video makers at the time.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Shine Louise Houston: An Interstice of Her Own Making - Stallings, L. H. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
It is the twenty-first century, and there is a black lesbian director and producer making pornography! Porn, a genre of film and media that in the last quarter of the twentieth century many black feminist lesbians viewed as capable only of representing and manifesting violence, abuse, and shame. In this essay I examine one of the early works of the black lesbian filmmaker Shine Louise Houston, In Search of the Wild Kingdom (2007), to explore how and why we have arrived at what is a transition from Blues Legacies and Black Feminisms to Pink and White Productions, and from New
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Creating the World Anew: Black Lesbian Legacies and Queer Film Futures - Gumbs, Alexis Pauline (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Deeply grounded in the legacy of Black lesbian artists, writers, and filmmakers, current Black lesbian filmmakers are helping to build infrastructure for a transformed future using deeply interconnected methods to transform the whole world and (while we’re at it) the meaning of life. This chapter looks at two projects, the established and evolving Queer Women of Color Media Arts Project based in San Francisco and the emerging Queer Renaissance and Black Feminist Film School Project based in Durham, North Carolina, as examples of the robust future of Black lesbian filmmaking as a transformative community-building practice. The Queer Women of Color
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Narrating Our History: Selections from a Dialogue among Queer Media Artists from the African Diaspora - Ferrera-Balanquet, Raúl; Harris, Thomas Allen; Frilot, Shari; Gilliam, Leah; Suggs, Dawn; Taylor, Jocelyn; Welbon, Yvonne; Juhasz, Alexandra (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The first time I spoke in public about my work was during the Los Angeles Lesbian and Gay Festival in 1990. Cheryl Dunye was the only other woman of color on the panel. When I asked a question regarding funding, I naïvely stated that funding was not a prob lem for me considering the fact that my work at that time was of medium to low production quality. I had minimal access to a low-end production facility, and my piece was only five minutes long. I was alluding to the fact that it has been “easy” for me.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé